Penerapan Teknologi Rel Kereta Api di Sumatera Barat - Aulia Rahman (Analisis Sejarah, 2024)
This study examines the application of railway technology in West Sumatra, focusing on the challenges and innovations during the colonial period. The research aims to explore the historical context, technical developments, and socio-economic impacts of the railway construction in this region. Using a historical method with a qualitative approach, the study analyzes primary sources such as colonial archives and technical reports, along with secondary sources like historical books and scholarly articles. The findings highlight the introduction of rack railway systems to navigate steep terrains, demonstrating Dutch colonial technical prowess. Additionally, the construction of the Ombilin coal mines and the associated railway network significantly boosted the local economy but also revealed the exploitation of labor. Overall, the study provides insights into the interplay between technology, colonialism, and local society, emphasizing the importance of geographical adaptation in infrastructure development.